THE EFFECTS ON FLAXSEED (LINUM USITATISSIMUM) ON THE SEVERITY LEVEL OF ACNE VULGARIS. - Devi Saviera Firnanda; Asih Budiastuti; Aryoko Widodo; Dhega Anindita Wibowo (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2020)
Introduction. Acne vulgaris is the formation of blackheads, papules, pustules, nodules, or cysts which were the result of the blockage and inflammation of the pilosebaceous unit. In general, there are several factors associated with the occurrence of Acne vulgaris, namely the abnormal activity of the bacterium Propionibacteria acnes, increased sebum production, hyperkeratinization of the pilosebaceous duct, and also the inflammatory process. Objectives. The primary objective of this research is to know the effect of flaxseed (Linum usitatissimum) on the severity level of Acne vulgaris. Methods. The design of this research is experimental research with a one-group pre-test post-test design. This research will be conducted from October to November 2019. And will be implemented in the city of Semarang. The population in this research is female college students (preferably Diponegoro University students) aged 18-23 years old who suffered from various severity degrees of Acne vulgaris which fulfills the inclusion and exclusion criteria. Subjects are determined using purposive sampling methods. Results. The research sample was mostly females aged 18-23 years of 2016 at Diponegoro University who suffered from various degrees of Acne vulgaris. After a paired T-test, p <0.05 was obtained. Because the results obtained are p <0.05, it can be concluded that there is a significant difference between the degree of Acne vulgaris during the pre-test and post-test. Conclusion. there is an effect of Linum usitatissimum seeds on the severity of Acne vulgaris.